Contextualizing Islamic Education: Value Transformation and Religious Moderation in Bonokeling's Dual Authority System - Ivana Maulia Rahmah; Muh Hanif (Papanda Publisher, 2026)
The integration of Islamic teachings with local religious traditions in rural Indonesia presents a compelling phenomenon warranting sociological investigation. This study examines the transformation of Islamic Religious Education (PAI) values within the Bonokeling indigenous community in Banyumas, where adherents simultaneously maintain ancestral rituals while internalizing formal Islamic values. This qualitative-descriptive research employed sociology of religion framework, utilizing participatory observation, in-depth interviews with key informants (Bedogol/Kyai Kuncen, religious teachers, students), and documentary study. Data were analyzed through thematic analysis guided by symbolic interactionism. Findings reveal a significant transformation from mystical ritualism toward rational social spirituality across five dimensions: religious focus, knowledge transmission, religious understanding, worship participation, and religious identity. The community successfully creates harmonious coexistence between formal Islamic teachings and local traditions through practices such as pengajian, ziarah, and slametan. A dual authority structure of kiai and customary leaders facilitates effective contextualization and transmission of Islamic values (tawāḍu', ukhuwah, ta'āwun). The Bonokeling community exemplifies authentic religious moderation grounded in local wisdom, demonstrating that local traditions function as effective pedagogical vehicles. This model enriches Islamic educational sociology by challenging formal-informal dichotomies and offering evidence-based insights for developing culturally-contextualized Islamic education promoting inclusive religiosity while maintaining theological orthodoxy.